Improvement of coordination abilities of sportsmen of 13–15 years old in fighting sambo - Батєєва, Наталія Петрівна (Slobozhanskyi Herald of Science and Sport, 2016)
Bateyeva N. Purpose: to determine the level of coordination abilities of sportsmen of 13–15 years old in fighting sambo. Material & Methods: the following methods of the research were used: theoretical analysis and synthesis of data of special scientific and methodical literature; pedagogical supervision; pedagogical testing; methods of mathematical statistics. 12 sportsmen of fighting sambo are tested for ability of support of static and dynamic balance before and after the pedagogical experiment. Results: the metrological control of coordination abilities of sportsmen of fighting sambo is considered. The individual estimated results are received on ability of support of static and dynamic balance. The dynamics of the level of the development of coordination abilities of sportsmen of 13–15 years old in fighting sambo is defined. Conclusions: the positive changes of the level of the development of coordination abilities, which are received under the influence of a technique of improvement of statodynamic firmness and sensomotor coordination, allow us to recommend this technique for application in the educational-training process of sportsmen of fighting sambo.